Optimal decisions of sharing rate and ticket price of different transportation modes in inter-city transportation corridor - Zhaoping Tang; Jin Qin; Huan Liu; Xiang Du; Jianping Sun (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The paper concerns competition of different transportation modes coexist in inter-city transportation corridor. The purpose of this paper is to express the competitive relationship by building mathematical model and obtain the best sharing rate and the optimal ticket price of different transportation modes. Design/methodology/approach: Firstly, analyzing influencing factors of passenger choice about transportation modes, we designed an utility function of transportation modes. Secondly, referring to the game theory and logit modle, a non-cooperative game model between railway and highway was built. Finally, the model was applied to Nanchang-Jiujiang transportation corridor in China for an empirical analysis. Findings: The results indicate that the proposed non-cooperative game model is rational and reliable, and it supplies a scientific method to determine the optimal ticket price and passenger sharing rate of different transportation modes, and can be applied to the competition study on different transportation modes in inter-city transportation corridor. Originality/value: The main contribution of this paper is to built the non-cooperative game model, which can consider the needs of different travelers, and achieve reasonable passenger divergence of different transportation modes and coordinated development of whole transport market.
Keywords: 650; transportation corridor; game model; sharing rate; ticket price